Contribuições do ensino da Física na formação do engenheiro civil - Souza, Maud Rejane de Castro e (2016)
The Civil Engineering Course has a high failure rate in the subjects of the basic cycle, according to the researchers of the area one attributed causes is related to the discipline of Physics that is delivered in a decontextualized way and unrelated to the professional disciplines, the excess of theory at the beginning and postponement of practical experience discourage students, who fail several times, many drop out (43%) and most students who complete the course do not perform well. In order to contribute to the resolution of this problem we first made a bibliographical survey of the support of the Physics Teaching trajectory in the Engineering Courses, where we carried out the literature review of the area, besides the documentary analyzes of the Pedagogical Projects of the Courses, National Curricular Guidelines and Plans of Teaching of Physics. Following with a diagnostic evaluation of the teaching of physics in Civil Engineering courses, for this we investigate the conceptions of the students, coordinators and teachers, through a questionnaire and interviews and through the Delphi Method we validate a Proposal of the teaching of Physics for the development of ability and skills necessary for the professional practice of the Civil Engineer. The methodology used in the research was the mixed exploratory sequential design.